Comparative Study of Temporalis Fascial Graft Medial or Lateral to Handle of Malleus in Tympanoplasty - Debnath, Timir Kumar; Hazari, Aslam; Arefeen, Shahinur; Rahman, Wakilur; Datta, A K; Samad, Abdus (Bangladesh Journal of Otorhinolaryngology, 2023)
Objective: To asses and compare the hearing outcome and healing of Temporalis fascia graft in both groups by placing the graft medial (underlay technique) or lateral to the handle of malleus (over- underlay technique). Method: This retrospective study conducted for a period January,2018 to December 2019- Two years period in Specialized ENT Hospital (SENTH) of SAHIC (Society for assistance to hearing impaired Children), Dhaka. It includes 104 patients, Group-A 59 patients (Underlay technique) and Group-B 45 patients (Over-underlay technique). Result: Graft success rate overall 84.62%, Group-A- 84.75% (Medial to malleus) and Group-B- 84.44% (lateral to malleus). Pre- and post- operative air- bone gap of two groups were compared. Conclusion: Both techniques (medial or lateral to malleus handle) has a high rate of success for the closure of TM perforation with significant improvement in air-bone gap. Bangladesh J Otorhinolaryngol 2023; 29(1): 17-23